A comparative study of hemicellulose isolation with hot water, alkaline, and delignification methods from tea leaf brewing waste - Tasar, Seyda; Ozer, Ahmet (Springer Heidelberg, 2022)
Tea leaf brewing waste (TLBW) is a waste with high hemicellulose content. It is a valuable waste of the pharmaceutical and cosmetics industry especially the beverage industry. In this study, the extraction of hemicelluloses (HC) from tea leaf brewing waste using three different pretreatment methods were investigated. The isolation yield of the HC was determined depending on pretreatment methods and pretreatment parameters such as the isolation temperature (25-55 degrees C), alkaline concentration (NaOH, 5-20%), contact time (12-24 h), the oxidative component (H2O2), and the concentration of sodium chlorite (NaCIO2) in the solution (2-10%). It was observed that the yield of isolation of hemicellulose varied between about 1 and 36% on the basis of raw materials depending on the extraction parameters. The experimental results showed that the suitable conditions for isolation of hemicellulose by alkaline pretreatment method were 15% NaOH concentration, 12-h contact time, and 45 degrees C. As a result of the experiments performed with the most suitable conditions, approximately 96% of the total hemicellulose in the TLBW was isolated. The extraction yield of hemicellulose achieved by the delignification process was found to be lower about 3% compared with the alkaline methods. But, the hemicellulose color achieved by the delignification process was lighter in color than the alkaline method. The results of the FTIR and H-NMR analysis show that the purity of the hemicellulosic fraction, which was obtained using the delignification method, was higher than the alkaline method.
Keywords: Tea leaf brewing waste; Hot water process; Alkaline-oxidative process; Delignification process; Isolation of hemicellulose